2001
DOI: 10.1021/jm0010320
|View full text |Cite
|
Sign up to set email alerts
|

Heterocycle-Containing Retinoids. Discovery of a Novel Isoxazole Arotinoid Possessing Potent Apoptotic Activity in Multidrug and Drug-Induced Apoptosis-Resistant Cells

Abstract: In a search for retinoic acid (RA) receptor ligands endowed with potent apoptotic activity, a series of novel arotinoids were prepared. Because the stereochemistry of the C9-alkenyl portion of natural 9-cis-RA and the olefinic moiety of the previously synthesized isoxazole retinoid 4 seems to have particular importance for their apoptotic activity, novel retinoid analogues with a restricted or, vice versa, a larger flexibility in this region were designed and prepared. The new compounds were evaluated in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 39 publications
2
42
0
1
Order By: Relevance
“…The induction of apoptosis after combined treatment with 5-Aza-dCyd and ATRA is possibly explained by retinoic acid acting on the demethylated cell population generated after 5-Aza-dCyd treatment. The K562 cell lines was previously reported to be resistant to differentiation induction by ATRA (23,24). Similar results were obtained when we studied other cell lines, such as the breast cancer cell lines CAMA-1 and BT-474, but using 1 M of ATRA after only 0.1 M of 5-Aza-dCyd instead of 1 M as in the cell line K562.…”
Section: Discussionsupporting
confidence: 87%
“…The induction of apoptosis after combined treatment with 5-Aza-dCyd and ATRA is possibly explained by retinoic acid acting on the demethylated cell population generated after 5-Aza-dCyd treatment. The K562 cell lines was previously reported to be resistant to differentiation induction by ATRA (23,24). Similar results were obtained when we studied other cell lines, such as the breast cancer cell lines CAMA-1 and BT-474, but using 1 M of ATRA after only 0.1 M of 5-Aza-dCyd instead of 1 M as in the cell line K562.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the indole residue may be substituted by either the pyrrole (analog 13) or the 4-amino-9-fluorenone (analogs 14 and 15) moieties, whereas structural characteristics of the two types of ACI analogs may be combined as exemplified with analog 16. Earlier studies have shown that inclusion of aromatic heterocyclic rings in retinoids is associated with reduced toxicity [5]. The involvement of these particular heterocyclic rings in the design of our analogs stemmed from the anticipation that they could be readily incorporated into the spacer by using the commercially available indole-3-carboxylic acid and -carboxaldehyde or the readily synthesized 3-acetylpyrrole, which include the hydrolytically stable N-C]C-CO structural motif.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Heteroaromatic rings have been included as central retinoid linkers less frequently. [14,[16][17][18][19] We therefore set out to design, synthesize and assess the ligand binding of a collection of retinoids that have a pyrazine heterocycle as a central connecting unit. To meet the structural requirements for RAR or RXR selectivity, we focused on two series of positional isomers that are derived from 2,3,6-and 2,3,5-trisubstituted pyrazines (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%